If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6ln(x + -3) = 1 Reorder the terms: 6ln(-3 + x) = 1 (-3 * 6ln + x * 6ln) = 1 (-18ln + 6lnx) = 1 Solving -18ln + 6lnx = 1 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Reorder the terms: -1 + -18ln + 6lnx = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -18ln + 6lnx = 0 The solution to this equation could not be determined.
| 10-3-60=80 | | 3x+3-5x=15+4x | | 11(4x+3)=19 | | 30x^5-32x^4-4x^3-4x^2-14x-2=0 | | 4b+11=19 | | Dx+dy=0 | | 12-6-74=22 | | 5(2h+2)=5h | | 2x+3=2(3x-8) | | 1+4c=-15+8c+48 | | 143+6+8=67 | | 3x+2x-7=18 | | 3(2x-5)+20=-2(x+6) | | 5x-76+3x=148 | | 6x-5y+4=0 | | 7+4.7+-4.7=4.7 | | cos*4x*cos*2x=0 | | 7+4.7+-7=4.7 | | 5x=5(x+7) | | -6r+78r-18=60r+6 | | -x-25+4=50 | | Y^2+y-6=-3y+6 | | 7+4.7+4.7=4.7 | | 7+4.7+7=4.7 | | 0.75x=10 | | 7-2h=3 | | 11-106=2+38 | | 3x-10+2x=75 | | 19+23= | | 4x+6=2(18x+4) | | 42-19= | | 6+12=15+11 |